2008
DOI: 10.1080/08946560801973077
|View full text |Cite
|
Sign up to set email alerts
|

The Devil is in the Details: Self-Neglect in Australia

Abstract: Although elder self-neglect is of significant concern to adult protective service (APS) workers in the United States, minimal research has been conducted on this topic in Australia. Using qualitative research methods, this article examines how 24 Australian professionals understand situations of self-neglect. Unlike in the United States, where the term self-neglect is used in a broad and all-encompassing manner, participants in this research differentiated among self-neglect (the neglect of self), squalor (ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…In addition, the study did not have specific indicators of self-neglect to further explore the specific phenotypes of self-neglect and its associated factors. Prior work by McDermott [32] has also suggested the value of understanding specific behaviors of self-neglect. However, we believe that our present findings will set the groundwork for future studies to rigorously investigate these issues.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study did not have specific indicators of self-neglect to further explore the specific phenotypes of self-neglect and its associated factors. Prior work by McDermott [32] has also suggested the value of understanding specific behaviors of self-neglect. However, we believe that our present findings will set the groundwork for future studies to rigorously investigate these issues.…”
Section: Discussionmentioning
confidence: 99%
“…There is an immense diversity in the type of living conditions that are categorised as squalor (McDermott, 2008). Partly because of this diversity, these situations can pose tricky ethical and practical dilemmas for professionals whose role it is to support older people in the community.…”
Section: Dilemmas In Situations Of Squalormentioning
confidence: 99%
“…Sixth, we did not have specific indicators of self-neglect to further explore the relations between personality traits with specific phenotypes of self-neglect. Prior work by McDermott et al (47) has also suggested the values of understanding specific behaviors of self-neglect. Lastly, our study definition for elder self-neglect differs from prior studies.…”
Section: Discussionmentioning
confidence: 99%